Trzy dekady etyki biznesu w Polsce - Sójka, Jacek (Humaniora. Czasopismo Internetowe, 2024)
The origins of Polish business ethics were closely linked to the democratisation of the Polish political system and the economic transformation of the 1990s. These were formative years for Polish business ethics. The moral aspects of this transformation inevitably became the topic of the day, but also, especially within academic reflection, ethical analyses of the very nature of the market economy and more general questions about morality of capitalism began to emerge. This article recounts three decades of Polish business ethics, covering the 1990s and the first two decades of the 21st century. This story is primarily about people who were actively involved in promoting the new discipline and about institutions they created. However at the end of this period they may have been surprised to witness the political turmoil associated with the rise of populist and anti-liberal tendencies in Polish politics. The question of whether ethical business can exist in a non-democratic environment therefore recurs. However, the answer seems simple: without liberal democracy and the rule of law, ethical business standards will remain an impossible ideal.